Plasma oxalic acid as a trigger for oxidative processes in end-stage renal disease patients - L. Korol; N. Stepanova; V. Vasylchenko; L. Snisar; L. Lebid; M. Kolesnyk (Ukrainian Journal of Nephrology and Dialysis, 2021)
The present study aimed to evaluate the changes in oxidative stress markers according to the concentration of plasma oxalic acid (POx) in end-stage renal disease (ESRD) patients.Methods. We conducted a cross-sectional observational study involving 72 ESRD patients and 30 relatively healthy individuals who served as a control reference group for evaluation of POx concentration. Among ESRD patients there were 32 hemodialysis (HD) patients and 40 peritoneal dialysis (PD). POx concentration was measured spectrophotometrically using a commercially available kit (MAK315, Sigma, Spain). Malonic dialdehyde (MDA), ceruloplasmin (CP), transferrin (TR), sulfhydryl groups (SH-groups), antioxidant blood capacity (AOC) and total peroxidase activity of erythrocytes (TPA) were measured and the oxidative stress index (OSI) was calculated in all examined patients.Results. A significant increase in POx concentration was observed in ESRD patients compared with healthy volunteers (p < 0.0001). The concentrations of MDA in serum, OSI in erythrocytes and serum of the examined patients were gradually increased, while serum levels of CP, AOC, SH-groups and TPA in erythrocytes, on the contrary, were decreased in accordance with the increasing trend of POx concentrations. Correlation analysis demonstrated a statistically significant direct relationship between POx concentration and MDA (r = 0.57; p <0.0001) and OSI (r = 0.64; p <0.0001). The inverse correlation was determined between POx and antioxidant markers: CP (r = -0.35; p = 0.007), SH-groups in serum (r = -0.3; p = 0.04) and erythrocytes (r = -0.53 ; p <0.0001).Conclusions. The intensity of oxidative-antioxidant balance disorders in the blood of ESRD patients has been associated with the POx concentration: the higher the concentration of POx was the more active oxidative processes and the more pronounced lack of antioxidant protective factors occurred. Further studies are needed to determine the role of POx in the initiation of oxidative stress and chronic inflammation in ESRD patients.